Calculating the Power Demand in Turning of AISI 316L Stainless Steel Through the Cutting Forces Data - Nur, Rusdi (INTEK: Jurnal Penelitian, 2016)
Abstract—Austenitic stainless steel AISI 316L has been widely used for orthopedic implants due to its mechanical properties, corrosion resistance and biocompatibility. Machining of austenitic stainless steel are often regarded as 'difficult to machine' and classed a single group of steels, based on experience with the most common austenitic types. This paper presents a methodology for practical calculation of power demand based on cutting force that will be compared with experimental results especially turning process. Based on a previously proposed definition, the power demand in metal cutting is the energy required cutting. This paper provides a complete list of mathematical expressions needed for the calculation of power demand and demonstrates their utility for turning operation of austenitic stainless steel using coated and uncoated carbide.